Challenges And Solutions In Building Multicultural Education At Smk Sabilul Muttaqin Mojokerto: A Study Of Islamic Values - Fahman, Ahmad Amiq; Yusuf, Achmad; Ma’ruf, Ahmad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This research shows that multicultural values are implemented systematically through inclusive pedagogy,?diversity based curriculum, and instruction models which promote tolerance, inter-religion dialogue, and the strengthening of cultural identity. This article uses a descriptive qualitative approach to deeply understand the implementation of multicultural values in Islamic Religious Education (PAI) learning at Sabilul Muttaqin Vocational High School. The PAI teachers are the main protagonist in fostering?the value of respect for cultural and religious differences in the school environment. Yet, ongoing barriers such as racism against students and the lack of resources for education compromise potential for?effectiveness across these initiatives. The results of this study are to improve teacher capacity, for example by providing focused multicultural?training, and the creation of inclusive, diversity responsive teaching resources.